تحديد الاحتياجات التدريبية للقيادات الإدارية بالمصارف التجارية الليبية دراسة ميدانية - Samir Ibrahim Sulaiman Rwimed
The study aimed to identify the training needs of the administrative leaderships at Libyan commercial banks through knowing the degree of the availability of leadership skills (technical, human, administrative), and through knowing the importance of the training needs in each skill from the administrative leaderships’ standpoint. Moreover, the study tried to detect the impact of the identification of the training needs on the performance of the administrative leaderships. The population of the study included all the administrative leaderships in Libyan commercial banks. A purposive sample was selected which consisted of (275) administrative leaders who represent (members of the board of directors, general managers, administration managers, department heads, office managers) for five of the largest operating commercial banks in Libya. For the purpose of data collection, questionnaires were distributed to the leaders whereby the number of the received answers was (216). The descriptive analytical approach was used in the analysis of data. The most important findings of the study include; a decrease in the level of the technical leadership skills for the administrative leadership whereby the overall average of the degree of availability of the technical skills was (2.59), the relative weight was (%51.9) and a low degree of availability. The findings also revealed a medium level of human leadership skills of the administrative leadership whereby the overall average of the degree of availability of human skills was (3.01), the relative weight was (%60.2) and a medium degree of availability. In addition, the findings also indicated a decrease in the administrative leadership skills level whereby the overall average to provide a degree of administrative skills was (2.58), the relative weight was (%51.7) and a low degree of availability. They also showed that there were statistically significant differences at (α ≤0.05) between the degree of the significance of leadership skills and the degree of its availability. The findings also revealed that the most leadership skills in need of training were the skill of the administrative creativity with the size of the training gap reaching (1.95), followed by the evaluation performance skill with the size of the training gap reaching (1.90) and the organization skill with a size of the training gap reaching (1.83), respectively. However, the less leadership skills in need of training were the skill of stimulus in which the size of the training gap was (1.19) followed by the communication skill with the size of training gap approaching (.943), respectively